Effect of vanillic acid against oxidative stress induced by glyphosate in Saccharomyces cerevisiae - Özcan, Gözde; Demır, Ersın; Ökkeş,; Yılmaz, Okkes; Yilmaz,; Erişir, Figen Erdem; Zengin, Hatayi (My University, 2019)
Glyphosate is a widely used broad-spectrum herbicide. Vanilic acid is a phenolic acid found naturally in manyplants. In this study, the effect of vanilic acid against oxidative stress induced by glyphosate in Saccharomyces cerevisiaewas investigated. S. cerevisiae was proliferated and developed in YEDP medium. Both glyphosate and vanilic acid wereadded to the development environment of Saccharomyces cerevisiae to be 200, 400 and 800 mg per liter. At the end ofthe experiment, Saccharomyces cerevisiae samples (Reduced glutathione (GSH), oxidized glutathione (GSSG),Malondialhedit (MDA), fatty acid, E, D, K vitamins and phytosterol) were analyzed in HPLC and GC devices.Antioxidant potential of vanillic acid was also identified. In this study, the effect of vanillic acid against oxidative stressand toxicity caused by glyphosate in S. cerevisiae was investigated for the first time. In S. cerevisiae administeredglyphosate, there were statistically significant changes in MDA, GSH, GSSG, protein, fatty acid, E, D, K vitamins andphytosterol levels, but the vanilic acid applied was detected statistically significantly reduced the changes in theseparameters. As a result of analysis by gas chromatography, the yeast cell of octanoic acid (8: 0), lauric acid (12: 0),myristic acid (14: 0), palmitic acid (16: 0), palmitoleic acid (16:1 n-7), stearic acid (18: 0), oleic acid (18:1 n-9) andlinoleic acid (18:2 n-6) acids were observed. Vitamin D, E and K were analyzed with HPLC device. As a result of thisanalysis, molecules such as K2, ?-tocopherol, D2, D3, ?-tocopherol, ergosterol, K1, stigmasterol, ?-sitosterol wereidentified. Biochemical analysis showed that cell density in culture medium containing 800 mg per liter of glyphosatedecreased. It was found that vanilic acid showed beneficial effects against oxidative stress caused by glyphosate inSaccharomyces cerevisiae.
Keywords: Biyoloji; Mantar Bilimi; Kimya; Tıbbi